Sinkers or floaters? Contribution from salp pellets to the export flux during a large bloom event in the Southern Ocean. (April 2017) - Iversen, Morten H.; Pakhomov, Evgeny A.; Hunt, Brian P.V.; van der Jagt, Helga; Wolf-Gladrow, Dieter; Klaas, Christine
Abstract: Salp fecal pellets are rich in organic matter and have been shown to sink at very high velocities. In recent years, salp abundances have been increasing in the Southern Ocean where they seem to be replacing krill as the dominant grazers on phytoplankton. As salps can form large swarms with high pellet production rates, it has been suggested that they will become increasingly important for the vertical export of particulate organic matter in the Southern Ocean. However, detailed studies combining both investigations of pellet production rates, turnover, and export are still needed in order to determine whether salp pellets are important for export ('sinkers') or recycling ('floaters') of organic matter. Our results suggest that pellets are produced at high rates in the upper few hundred meters of the water column. Although we observed high sinking velocities and low microbial degradation rates of the produced salp pellets, only about one third of the produced pellets were captured in sediment traps placed at 100 m and about ~13% of the produced pellets were exported to sediment traps placed at 300 m. The high retention of these fast-settling pellets seems to be caused by break-up and loosening of the pellets, possibly by zooplankton and salps themselves. We measured 3-fold lower size-specific sinking velocities in loosened and fragmented compared to freshly produced intact pellets-. This enhanced the residence times (>1 day) of both small and large pellets in the upper water column. We postulate that the fragile nature of salp pellets make them more important for recycling of organic matter in the upper mesopelagic layer rather than as a conduit for export of particulate organic matter to the seafloor.